(untitled) (University Arena, 2025)
Why do people see tennis as a clean sport? The simple answer is that very few players ever test positive for banned substances. The ITF spends 4m a year on anti-doping. Over 50m is awarded in prize money at the US Open alone, with each champion this year taking home 3.7m. Given how much financial value is placed on the appearance of cleanliness, you can see why the sport might think this economic model works.